LC-ESI-MS profile, antioxidant activity and cytotoxic screening of Oligomeris linifolia (Vahl) Macbr. (Resedaceae) - Ali M. El-Hagrassy, Ahmed Elkhateeb, Sameh R. Hussein, El-Sayed S. Abdel-Hameed & , Mona M. Marzouk (Journal of Applied Pharmaceutical Science, 2017)
LC-ESI-MS analysis was investigated for the n-butanol, methanol and water fractions of Oligomeris linifolia, which leads to the identification of twenty-one compounds, among them sixteen compounds were firstly reported from this plant and five compounds were identified previously. Butanol and methanol fractions showed higher antioxidant activity with IC50 values of 10.37μg/ml and 31.07μg/ml, respectively, compared with that of the standard; Trolox (33.55μg/ml) using DPPH method. However, water fraction showed lower activity (IC50: 91.86 μg/ml). The three fractions were also screened for their cytotoxicity and showed weak effect against HCT116, A549 and MCF7 at 100 mg/ml and no effect against HEPG2.
Keywords: Oligomeris linifolia, phenolics, flavonoids, LC-ESI-MS, Antioxidant, Cytotoxicity.